Administrative dimensions in the regulation of occupational health and safety focus on the Bureau of Working Conditions - Bautista, Victoria A. (1989)
The paper primarily focuses on the strategies, resources and performance in the enforcement of Occupational Health and Safety (OHS) by the Bureau of Working Conditions (BWC) of the Department ofLabor andEmployment (DOLE) - the lead agency of government charged with the regulation of OHS in the Philippines. More specifically, it dwells on the regulatory process itself and other support activities for enforcement such as planning and technical supervision, research, information dissemination, monitoring and evaluation. It also offers policy recommendations towards the enhancement of OHS in the Philippines.
Keywords: Industrial hygiene; Occupational health services; Bureau of Working Conditions